3(x+9)=5(x-1)

Simple and best practice solution for 3(x+9)=5(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+9)=5(x-1) equation:



3(x+9)=5(x-1)
We move all terms to the left:
3(x+9)-(5(x-1))=0
We multiply parentheses
3x-(5(x-1))+27=0
We calculate terms in parentheses: -(5(x-1)), so:
5(x-1)
We multiply parentheses
5x-5
Back to the equation:
-(5x-5)
We get rid of parentheses
3x-5x+5+27=0
We add all the numbers together, and all the variables
-2x+32=0
We move all terms containing x to the left, all other terms to the right
-2x=-32
x=-32/-2
x=+16

See similar equations:

| 1.5=(1+r)^10 | | 8x+4=62 | | 5x/8=2x+3/4 | | 5h–30=138 | | –6(2x+3)=–12x–18 | | 8x–7=6x+22 | | 63=-9(y-100) | | 10-(x-8)=3x+4x+1 | | 4(x+3)=2(x+4)+2(x+1) | | 5h=9 | | 80-2x=180 | | (7x+5)(8x-8)=180 | | 2^x=1.41421 | | p+6p−3p+5p=−36 | | 80-4x=180 | | 2=b/9-3 | | 3n+4=54 | | 21=16+x | | 180=80-2x | | x^2+2x+4=3x+10 | | 3x-6+4=2 | | 6.5z=104 | | x^2-6x=48+2x | | 180=80-4x | | 2=r-71/10 | | -y+750=805 | | 4y+5−2y+3=16 | | 2.5+x=-15.6 | | -2(w+4)=-12 | | 5(x-9)=13+3x | | 5x+7-18x=14+3x-18 | | -9.8j-9.14=-5.6j-9.14+6.8j |

Equations solver categories